Food insecurity during pregnancy leads to stress, disordered eating and greater postpartum weight among overweight women - Laraia, Barbara (Obesity (Silver Spring), 2015)
OBJECTIVE: We sought to understand the influence of food insecurity on women's stress, disordered eating, dietary fat intake and weight during the postpartum period. Design and Methods: We estimated the association between marginal food security and food insecurity—measured during pregnancy and postpartum—and stress, disordered eating, dietary fat intake and weight at 3 and 12 months postpartum using multivariate linear regression, controlling for demographic and socioeconomic characteristics and health behaviors. We assessed effect modification between level of food insecurity and prepregnancy weight status, hypothesizing a stronger association would be found among women who started pregnancy overweight or obese. RESULTS: Food insecurity status during pregnancy was strongly associated with higher levels of stress, disordered eating, and dietary fat intake at 3 and 12 months postpartum; during the postpartum period it was associated with these measures at 12 month postpartum. A significant interaction was found between level of food insecurity and prepregnancy weight status; food insecurity was associated with greater weight and BMI at 12 months only among overweight/obese women. CONCLUSIONS: In order to return to one's prepregnancy weight, overweight and obese women who face household food insecurity may need multipronged assistance that addresses not only having enough high quality food, but include stress reduction and eating behavior interventions.